THE INFLUENCE OF MONETARY POLICY ON THE FINANCIAL RECOVERY OF BANKS - Stadniychuk, Roman (Socio-economic relations in the digital society, 2020)
This article substantiates the need to use monetary policy in the financial recovery of banks. Its role in the period of crisis phenomena in the economy and in the banking system, the composition of monetary instruments and their features are determined. It is substantiated that in the conditions of stabilization of the domestic banking sector the regulatory direction of the NBU actions was aimed primarily at supporting the liquidity of the banking system of Ukraine through intensification of refinancing mechanisms, changes in reserve policy, restraining the outflow of funds outside the banking system. Monetary instruments that had a direct impact on the financial recovery of banks in the study period are considered — the discount rate, required reserves, repo transactions, purchase and sale of government securities, swap transactions. An analysis of dynamic changes in the discount rate as the main monetary instrument, according to which the NBU sets a benchmark for money market participants on the value of borrowed and placed funds for the period, revealed the benefits of lowering the discount rate for banks and the economy. The use of the NBU as a lender of last resort to maintain the liquidity of banks at the required level is a tool such as refinancing their active operations. The peculiarities of its use by the NBU and the evolution of changes to date have been clarified. The role of operations of purchase (granting liquidity) and sale (withdrawal of liquidity) of government securities carried out by the NBU to support the liquidity of banks has been clarified. The regulator proposes to use effective monetary instruments and measures to ensure the smooth functioning of the banking system. Thus, banks entered the pandemic period without significant imbalances, sufficiently capitalized and highly liquid. The work to clean up and increase the stability of the banking system, carried out since 2015, has yielded an undeniable positive result. On the contrary, they have supported business and will help restore economic growth in the future by providing loans. Since the crisis unfolded, most banks have quickly shifted to working online. Despite the temporary reduction in the number of operating branches, the availability of banking services has not decreased.